Effects of Storybird-Based Digital Storytelling on Elementary School Students' Folktale Narrative Writing Performance - Halimatussakdiah; Fendy Yoga Pratama; Nurmayani; Laurensia Masri Pa; Naswa Amirah; Sonia Miranda Simorangkir (WISE Pendidikan Indonesia, 2026)
The transmission of regional cultural heritage to younger generations has become increasingly challenging amid globalization and the limited use of innovative instructional media in primary education. This study examined the effectiveness of Storybird-based digital storytelling in improving elementary school students' folktale narrative writing performance using “The Legend of Lake Toba” as instructional content. A quantitative one-group pretest–posttest design involved 35 elementary school students (N = 35, df = 34). Writing performance was assessed in terms of characterization, plot organization, and thematic development. Descriptive statistics and a paired-samples t-test were applied after the normality of the paired difference scores had been verified using the Lilliefors test. The mean writing score increased from 5.72 at pretest to 8.13 at posttest on a 10-point scale. This improvement was statistically significant, t(34) = 8.092, p < .001, 95% CI [1.80, 3.02], with a large paired-samples effect size (Cohen's d_z = 1.37). Storybird's visual prompts and sequential structure appeared to scaffold idea generation and narrative organization, with the largest improvement observed in characterization. These findings indicate that integrating local cultural content with multimodal digital storytelling can strengthen elementary students' narrative writing performance; broader claims concerning cultural preservation require direct measurement in future research.